Cataract Surgery with or without Intraocular Lens Implantation in Pediatric Uveitis: A Systematic Review with Meta-Analyses. (11th June 2021) - Schmidt, Diana Chabané; Al-Bakri, Moug; Rasul, Asrin; Bangsgaard, Regitze; Subhi, Yousif; Bach-Holm, Daniella; Kessel, Line
Abstract : Purpose . To systematically review the results of comparative studies of modern cataract surgery in pediatric uveitis with or without intraocular lens (IOL) implantation and to perform comparative meta-analyses to compare visual acuity outcomes and complication rates. Methods . On 12 November 2020, we systematically searched the Cochrane Central, PubMed/MEDLINE, EMBASE, ClinicalTrials.gov, and all affiliated databases of the Web of Science. Two authors independently reviewed studies and extracted data. Studies were reviewed qualitatively in text and quantitatively with meta-analyses. Outcome measures were preoperative and postoperative best-corrected visual acuity (BCVA), inflammation control, and rates of postoperative complications. Results . Ten studies of 288 eyes were eligible for review of which the majority were eyes with juvenile idiopathic arthritis-associated uveitis. Summary estimates revealed that the BCVA was better in pseudophakic eyes vs. aphakic eyes (1-year postoperative: −0.23 logMAR, 95% CI: −0.43 to −0.03 logMAR, P = 0.027 ; 5-year postoperative: −0.35 logMAR, 95% CI: −0.51 to −0.18 logMAR, P = 0.000036 ). Pseudophakic eyes had more visual axis opacification (OR 6.76, 95% CI: 2.73 to 16.8, P = 0.000036 ) and less hypotony (OR 0.19, 95% CI: 0.04 to 0.95, P = 0.044 ). Conclusions . In modern era cataract surgery on eyes with pediatric uveitis with IOL implantation leads to satisfactory and superior visual outcomes and no differences in complication rates apart from an increased prevalence of visual axis opacification and a decreased prevalence of hypotony when compared to aphakia. However, limitations of the retrospective design and the presence of selection bias necessitate a careful interpretation.